2001
DOI: 10.1034/j.1399-302x.2001.160608.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between betel quid chewing, periodontal status and periodontal pathogens

Abstract: The present investigation examined whether an association exists between betel quid chewing and signs of periodontal disease and determined the prevalence of Actinobacillus actinomycetemcomitans and Porphyromonas gingivalis by polymerase chain reaction. The periodontal status of 34 betel quid chewers and 32 non‐betel quid chewers were compared. A significantly higher prevalence of bleeding on probing was found in betel quid chewers than non‐chewers among the subjects with higher plaque level, greater gingival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 34 publications
3
63
2
Order By: Relevance
“…A possible contributing mechanism in the development of severe periodontal disease is the cholinergic effect of toombak along with the calcium salt in the saliva produced during hypersalivation causing calculus deposition. The heavy calculus deposition can then destroy periodontal tissue in smokeless tobacco users [6]. This finding is confirmed by a case report presented by Giri et al [7], which showed that smokeless tobacco in the form of betel nut chewing is associated with advanced periodontal tissue loss.…”
Section: Discussionsupporting
confidence: 72%
“…A possible contributing mechanism in the development of severe periodontal disease is the cholinergic effect of toombak along with the calcium salt in the saliva produced during hypersalivation causing calculus deposition. The heavy calculus deposition can then destroy periodontal tissue in smokeless tobacco users [6]. This finding is confirmed by a case report presented by Giri et al [7], which showed that smokeless tobacco in the form of betel nut chewing is associated with advanced periodontal tissue loss.…”
Section: Discussionsupporting
confidence: 72%
“…1,2 In addition, longterm BQ chewing may also cause inflammatory periodontitis and root fracture. 19,20 More seriously, ANE-induced inflammatory reactions are important for human response to infection, irritation, and injury, as well as to oral cancer. 7,21 AN not only induces oral epithelial hyperplasia and carcinogenesis, but also has an impact on subcutaneous connective tissue resulting in OSF.…”
Section: Discussionmentioning
confidence: 99%
“…It may well raise the suspicion that some chemicals from these chewing substances may trigger specific biochemical reactions related to dyslipidemia and hypertension, which in turn lead to cardiovascular events. In addition, chewing itself may lead to susceptibility to periodontal diseases, which are potentially associated with cardiovascular malfunction (Ling et al, 2001;Janket et al, 2003). The detailed mechanism by which these processes are involved in the development of CVD remains unclear and merits further investigation.…”
Section: Discussionmentioning
confidence: 99%